Adolescents' preference for later school start times. (13th June 2021) - Werner, Helene; Albrecht, Joëlle N.; Widmer, Natacha; Janisch, Daniel; Huber, Reto; Jenni, Oskar G.
Summary: As the chronotype delays progressively throughout puberty, early morning school start times (SSTs) contradict the sleep biology of adolescents. Various studies have demonstrated beneficial effects of later SSTs on sleep and health; however, adolescents' preferences for SSTs have to date never been investigated in detail. The present online survey study aimed to fill this gap and explored influencing factors. A total of 17 high schools in the Canton of Zurich, Switzerland, circulated the survey among their students. Participants were included if they reported their sex, age, and school ( n  = 5, 308). Students indicated whether they preferred later SSTs. Additionally, five predictor blocks were assessed: sociodemographic, school‐related, sleep, leisure‐time, and health‐related characteristics. We applied multivariate logistic regression models with fixed and random effects to predict the preference. The mean ( SD ) age of the students was 16.09 (1.76) years (65.1% female). The majority (63.2%) endorsed later SSTs with a preferred delay of 55 min (interquartile range 25–75 min). In the multilevel analysis ( n  = 2, 627), sex, mother tongue, sleep characteristics, mobile device use at bedtime, caffeine consumption, and health‐related quality of life were significant predictors for the preference. Hence, the majority of adolescents preferred later SSTs, and especially those with sleep or health‐related problems. These characteristics have been consistently shown to improve after delaying SSTs. Thus, also from adolescents' view, later SSTs should be considered to improve the adolescents' health.